Economic Policy within a European Monetary Union - Alfred Pfaller (Intereconomics, 1991)
A European Monetary Union (EMU) and the complete transfer of the responsibility for monetary policy to a European central bank are no longer utopian ideas, but a politically highly relevant possibility. The question how economic policy goals can be achieved within such a monetary union is therefore gaining in importance.
Keywords: 330; European Community